Oral Dysbiosis and Autoimmunity: From Local Periodontal Responses to an Imbalanced Systemic Immunity. A Review - Suárez, Lina J.; Garzón, Hernan; Arboleda, Silie; Rodríguez, Adriana (Frontiers in Immunology, 2020)
The current paradigm of onset and progression of periodontitis includes oral dysbiosis directed by inflammophilic bacteria, leading to altered resolution of inflammation and lack of regulation of the inflammatory responses. In the construction of explanatory models of the etiopathogenesis of periodontal disease, autoimmune mechanisms were among the first to be explored and historically, for more than five decades, they have been described in an isolated manner as part of the tissue damage process observed in periodontitis, however direct participation of these mechanisms in the tissue damage is still controversial. Autoimmunity is affected by genetic and environmental factors, leading to an imbalance between the effector and regulatory responses, mostly associated with failed resolution mechanisms. However, dysbiosis/infection and chronic inflammation could trigger autoimmunity by several mechanisms including bystander activation, dysregulation of toll-like receptors, amplification of autoimmunity by cytokines, epitope spreading, autoantigens complementarity, autoantigens overproduction, microbial translocation, molecular mimicry, superantigens, and activation or inhibition of receptors related to autoimmunity by microorganisms. Even though autoreactivity in periodontitis is biologically plausible, the associated mechanisms could be related to non-pathologic responses which could even explain non-recognized physiological functions. In this review we shall discuss from a descriptive point of view, the autoimmune mechanisms related to periodontitis physio-pathogenesis and the participation of oral dysbiosis on local periodontal autoimmune responses as well as on different systemic inflammatory diseases.